(untitled) (Research, Society and Development, 2020)
The use of soy by-products in poultry feed has proven to be an important sustainable alternative, being capable of minimizing the environmental damage caused by the disposal of these residues and at the same time reducing the cost of production. However, for the use of these by-products in poultry feeding, it is necessary to know their chemical composition, antinutritional factors and also necessary measures to reduce these factors, as well as the best levels of inclusion that must meet the nutritional requirements of the animals in each production phase. In this context, the purpose of this review is to demonstrate the potential use of soy by-products (soy husk, soy acid oil, glycerin, soybean chopsticks, soy gum and okara) in the feeding of broilers, laying hens and cutting and laying quails, as well as the adverse effects that each can cause on animal performance. To carry out this review, analysis was carried out in several scientific studies that used soy by-products in the feeding of broilers and laying hens. It can be concluded that the potential for using soy by-products in Brazil is enormous, which expands the alternative ingredients that can replace soybean meals in poultry feed, without causing damage to performance, intestinal health, biochemical and hematological parameters, in addition to reduce the environmental pollution generated by the inappropriate disposal of these residues, as these ingredients could be a way to reduce the costs of diets.